Kurikulum dan Pendidikan Nasionalisme di Pondok Pesantren Tremas - Mukodi Mukodi (Institut Agama Islam Negeri Kendari, 2020)
This research aims to describe the curriculum design in Pondok Tremas; to measure the concept of nationalism in Pondok Tremas; to describe the nationalism education design of curriculum at Pondok Tremas; and make a model for strengthening nationalism in Pondok Tremas. This research is a grounded research model developed by Noeng Muhadjir with the naturalistic paradigm of Guba and Lincoln. The research sample was taken by using purposive sampling in Pondok Tremas Pacitan. The results showed that the curriculum design at Pondok Tremas is a salafiyah style (traditional) leading to seven santri daily activities, including: religious book reading, religious practices, musabaqah, implementation of reward and punishment, discussion, khitābiyah forum, and study of bahts al-masāil. The concept of strengthening nationalism in Pondok Tremas is carried out through the study of Kitab Kuning. The design of nationalism education in Pondok Tremas curriculum uses Ralph W. Tyler's development model theory, expressed through: thought (a study of Kitab Kuning), heart (in the form of wirid and istigatsah); feel (in the implementation of students’ five souls, including; simplicity, independence, brotherhood, freedom, modesty); and work (in the form of various community activities). The model of strengthening nationalism in Pondok Tremas is carried out through two domains: strengthening nationalism in the form of thought and strengthening nationalism in the form of action